NARASI PERJALANAN HIJRAH RASULULLAH DALAM BUKU SKI - Abdul Gani Jamora Nasution; Erina Damayanti; Khairunnisa, Khairunnisa; Syahrani Yumna Irfani (Jurnal Riset Rumpun Agama dan Filsafat, 2022)
This study aims to examine and explain the migration journey of the Prophet in the SKI book. This research uses library research methods or library research with a historical approach. Based on the results of the research, it was found that the meaning of hijrah was not merely an attempt to escape from trials and ridicule, but in addition to that meaning, hijrah was also intended as a stepping stone to establish a new society in a safe country, it also had the meaning of affirming the position of Muhammad and his followers. , with the previous era After the Prophet migrated to Medina, Islam developed rapidly. The Prophet made many agreements with non-Muslim groups such as the Prophet's agreement with the Jews of Medina and the agreement with the Quraysh infidels known as the Hudaibiyyah agreement. In addition, there were also many wars that took place between Muslims and infidels, such as the wars of badr, uhud, khandak, hunain, and fathul Mecca.